SISTEM PENDUKUNG KEPUTUSAN PRIORITAS CALON PENERIMA BANTUAN PROGRAM INDONESIA PINTAR (PIP) PADA SISWA TINGKAT SEKOLAH DASAR MENGGUNAKAN METODE MOORA - Manik, Laurensia Agustin; Maulita, Yani; Ambarita, Indah (UNIKA Santo Thomas, 2021)
Regarding assistance from the recipients of the Smart Indonesia Program (PIP) because there are so many prospective recipients of PIP assistance who volunteered to get the assistance, the process of delivering aid is sometimes not on target. Invalid data causes errors in the distribution of PIPs given to recipients who are entitled to receive them. Special Decision Support System (SPK) was built to support the solution of a problem or for an opportunity, one of the PIP aid recipient's approval in the Binjai City Education Office so that it is right on target for students who will get PIP assistance. The role of decision support systems is needed to improve the efficiency of decision making in determining students who are eligible for PIP assistance. The method used in this system uses the Multi-Objective Optimization method on the basis of Ratio Analysis (MOORA) and by using 7 (seven) criteria, namely family conditions, report card scores, parental work, number of dependents, number of dependents of children who attend school, home conditions and parents' income as well as 10 (ten) alternatives that are student data. Based on the results of calculations using the MOORA method, students on behalf of MM (A9) are the best alternative to be given PIP assistance with a value of 0.2843